Heterogeneous advanced oxidation processes over stoichiometric ABO3 perovskite nanostructures. (June 2022) - Mamba, G.; Mafa, P.J.; Muthuraj, V.; Mashayekh-Salehi, A.; Royer, S.; Nkambule, T.I.T.; Rtimi, S.
Abstract: The interest on single, stoichiometric ABO3 perovskites for heterogeneous advanced oxidation processes (AOPs) has grown in recent years because of their remarkable catalytic properties and versatile applicability. This review is devoted to highlighting and discussing the most recent developments and applications of ABO3 perovskites and their derived nanocomposites in water treatment and disinfection via AOPs. A brief overview of perovskites, with emphasis on ABO3 materials, their synthesis strategies, structure and properties, has been presented. More significant, the recent applications of ABO3 materials in photocatalysis, Fenton/photo-Fenton, persulphate activation, sonocatalysis/sonophotocatalysis, catalytic/photocatalytic ozonation, piezocatalysis/piezo photocatalysis and photoelectrocatalytic oxidation, has been well reviewed. Specifically, the catalytic activity of the ABO3 perovskites could be modulated through selection of the synthesis protocol and controlling the synthesis conditions, doping and co-doping of metal and non-metal ions, incorporation of carbon nanomaterials and heterojunction formation with other semiconducting materials. Furthermore, the use of ABO3 materials in conjunction with oxidants such as persulphate, H2 O2 and O3 yielded boosted activity of the hybrid processes compared with single processes. Details on the mechanisms of the charge carriers' formation and transfer in the different ABO3- mediated AOPs have been discussed to enhance the understanding of the degradation mechanism. Finally, some concluding remarks and outlook are detailed in terms of the general pitfalls and how they can be mitigated to provide guidance for future research and improve the exploitation of ABO3 perovskites in water treatment and environmental remediation applications. Graphical abstract: Image 1 Highlights: Review of recent advances in synthesis and application of ABO3 perovskites. Structural modification, doping, and heterojunction formation to improve the activity of ABO3 materials. Heterojunction photocatalysts show superior activity over single materials. Hybrid ABO3- mediated AOPs display better activity compared with classical AOPs due to synergy. Future considerations for successful exploitation of ABO3 perovskites are outlined.